ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS XII MIPA SMA NEGERI 4 PONTIANAK - Anshori, Muhammad; Hamdani, Hamdani; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to describe students? mathematical reasoning ability on the solid geometry matter of XII Grade MIPA SMA Negeri 4 Pontianak. The research method used was descriptive and the form of this research was case study. Subject of this research was students of XII MIPA 2 Class which consist 32 students. The techniques of data collection were mathematical reasoning ability test and interview. The results in this research shows that students? mathematical reasoning ability fall into the medium, low, and very low category, because there are 7 students (21,88%) were in very low category, 6 students (18,75%) were in low category, 17 students (53,13%) were in medium category, 2 students (6,25%) were in high category, and no students (0%) were in very high category. Some affect the students mathematical reasoning ability were in medium, low, and very low category because some students have not been able to form a conjecture and gives reason on their conjecture, most of the students can?t mathematic manipulating, and some students can?t finding a patterns against a mathematical phenomenon.Keywords: Mathematical Reasoning, Mathematical Reasoning Ability, Solid Geometry